Revolutionary Imaginaries and Legacies in Postrevolutionary Chinese Theatre: Amnesia, Nostalgia, Melancholia, Heterotopia, Cosmopolitanism - Chen, Chaomei (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2025)
This thesis is a study of postrevolutionary Chinese theatre from the 1980s to the 2010s to explore how revolutionary and socialist legacies, ruins, and memories are reimagined, re-membered, represented on the stage. I argue that mnemonic and representational schema of postrevolutionary Chinese theatre map onto five manifestations of the performative “palimpsest”—nostalgia, amnesia, melancholia, heterotopia, and socialist cosmopolitanism—to envision an alternative future by reimagining the past through theatrical aesthetics and practices. My research questions are as follows: what kinds of emotions and affects are expressed and articulated by Chinese theatre during the transitional periods from the Maoist socialist era to the Dengist early-reform era in the 1980s, and from the fin-de-siècle era to the 2010s? More broadly, how can a reconsideration of the relationship between theatrical aesthetics and politics serve to interact with, extend, or contradict the larger frameworks and paradigms set up by this global postrevolutionary phenomenon in different theatres, literatures, and cultures as a whole? More specifically, how can this study also contribute to the changing paradigms of Chinese theatre studies and the more general Chinese studies in a postrevolutionary, post-cold-war, post-globalization world? How can theatrical aesthetics and performing strategies disentangle the complexities between modernism and realism, between representation and history, between “return” and “exorcism” of the “spectres” of socialism and revolution? How can theatre reimagine and expand the public spheres in a depoliticized society? My research attempts to map multiple theatrical and performative configurations of socialism, revolution, colonialism, and capitalism at work jointly or in collision. My research materials are based on two fieldwork trips in Shanghai and a research visit to the East Asian Institute at the University of Vienna, where I collected recorded performance videos and published and unpublished scripts and reviews in the archives, as well as from individual artists, online and in-person interviews and communications with the artists, performance reviews published online and in academic journals. Apart from Theatre and Performance Studies, my interdisciplinary methodology also covers socialist literature, cultural politics, affective and psychoanalytic studies, political history, memory studies, hauntology, etc. My research will depart from, but also to be distinguished from, recent scholarship in both Chinese and Western theatre research on “representation”, memory, and “the real” and on representation of revolutionary and socialist histories (Ferrari 2023; Xiaomei Chen 2017; Chen et al. 2021; Rokem 2000, 2023; Reinelt 2013, 2019; Tomlin 2018; Tarryn Li-Min Chun 2021) and more general Chinese Studies (Jie Li 2016, 2020; Wang and Zhong 2014; Dai Jinhua 2009, 2018; Wang Hui 2009; Volland 2017; Yingjin Zhang 2015). Chapter 1 explores aesthetics and ideology regarding the contradiction between “socialist realism” and “capitalist modernism” in the early-reform era of the 1980s through the case study of WM (We) (1985). Chapter 2 explores the paradoxical despair- agency hidden in the left melancholy embraced by the New Left artists in the fin-de-siècle production of Che Guevara (2000-2001), through examining their reimagination of revolutionary utopia and socialist ideals in a resumption of leftist theatrical techniques. Chapter 3 investigates how the artists position the protagonist of The Crowd (2015) as a “hyper-historian” in Freddie Rokem’s notion, thus depoliticizing the political mass in the history of Chinese Revolution through their use of traditional Chinese pingtan and Brechtian aesthetics. Chapter 4 delves into how the Shanghai-based theatre collective Grass Stage’s World Factory draws on multiple leftist theatrical practices from different cultures to re-envision organic theatrical public spaces in postrevolutionary Chinese society through theatrical collaborations with workers. Chapter 5 explores how director iv Meng Jinghui and German dramaturg Sebastian Kaiser employ intercultural dramaturgy to reinterpret Lao She’s cosmopolitanism and socialist cosmopolitanism in 1950s Chinese literature and theatre through incorporating a polyphony of texts and intertexts of world literature and theatre.
APPROVED
Keywords: Chinese theatre, Postrevolution, leftist theatre, socialist legacy, amnesia, melancholia, heterotopia, nostalgia, cosmopolitanism